Malnutrition in Children: Analysis of Epidemiology, Risk Determinants and Advances in Management - Fehmina Arif; Muzammil Shabana Ejaz; Waseem Jamalvi (KARACHI MEDICAL AND DENTAL COLLEGE, 2017)
Malnutrition in children is one of the major health challenges faced worldwide but more frequently in South Asian countries including Pakistan. The objective of this review is to analyse the situation of malnutrition, its risk determinants, assessment and management strategies. This review is based on information collected from PubMed, Google scholar, Medline, World Bank, World Health Organization (WHO), United Nations Children's Fund (UNICEF) websites  and  books.  It  is  concluded  that  malnutri- tion status is improving but at  a  slower  pace.  Pakistan  has  a  high  prevalence  of  wasting,  stunting,  and micronutrient deficiencies.